2014
DOI: 10.1016/j.mce.2014.05.022
|View full text |Cite
|
Sign up to set email alerts
|

MiR-146b is a regulator of human visceral preadipocyte proliferation and differentiation and its expression is altered in human obesity

Abstract: Visceral obesity is an independent risk factor for metabolic syndrome, and abnormal fat accumulation is linked to increases in the number and size of adipocytes. MiR-146b was a miRNA highly expressed in mature adipocytes while very lowly expressed in human mesenchymal stem cells (hMSCs) and human visceral preadipocytes (vHPA). In this paper, we mainly focused on the roles of miR-146b in adipogenesis. We found miR-146b could inhibit the proliferation of visceral preadipocytes and promote their differentiation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
1
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 31 publications
6
71
1
3
Order By: Relevance
“…Among them, One hundred miRNAs were downregulated in late-laying-period hens, which suggested that those miRNAs may play important roles in gene upregulation. Previous studies demonstrated that miR-19b-3p [30], miR-425-5p [16], miR-27a [31], miR-146-5p [32], and miR-223 [33] influenced the differentiation of preadipocytes. We found that most of those miRNAs were DE miRNAs in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, One hundred miRNAs were downregulated in late-laying-period hens, which suggested that those miRNAs may play important roles in gene upregulation. Previous studies demonstrated that miR-19b-3p [30], miR-425-5p [16], miR-27a [31], miR-146-5p [32], and miR-223 [33] influenced the differentiation of preadipocytes. We found that most of those miRNAs were DE miRNAs in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…This is the case for miR-146b, which has been demonstrated to impair pre-adipocyte proliferation, thus promoting the transition to terminal differentiation and enhancing adipogenesis through direct targeting of KLF7 [25]. These findings demonstrate that miRNAs play an important role in both the induction and conclusion of the clonal expansion phase of adipogenesis as part of a complex and tightly regulated series of events required for proper adipocyte differentiation.…”
Section: Mirnas Regulating Pre-adipocyte Clonal Expansionmentioning
confidence: 93%
“…miR-21 has been shown to play a central role in the differentiation and function of both white and brown adipose tissue, and it is positively correlated with BMI in subcutaneous adipose tissue [89] . In preadipocyte proliferation, miR-146b is able to promote the transition to terminal differentiation, thus enhancing adipogenesis [90] .…”
Section: Role Of the Epigenetic Control: Mirnasmentioning
confidence: 99%